The Law of Healthcare Administration, Eighth Edition - Showalter, Stuart (AUPHA/HAP Book., 2017)
The Law of Healthcare Administration offers a thorough examination of health law in the United States from a management perspective. Using plain language accessible to nonlawyers, the book moves from broadbrush treatments of the US legal system and the history of medicine to specific issues that affect healthcare leaders daily, including contracts, torts, taxation, antitrust laws, regulatory compliance, and, most pressing, health insurance reform and the important changes that have taken place since the Affordable Care Act (ACA) became law in 2010. The legal concepts discussed in the book are amply supported by reallife examples, detailed explanations, and excerpts from decisions of federal and state courts.